Effect of nationwide reimbursement of real-time continuous glucose monitoring on HbA1c, hypoglycemia and quality of life in a pediatric type 1 diabetes population: The RESCUE-pediatrics study - De Ridder, Francesca; Charleer, Sara; Jacobs, Seppe; Bolsens, Nancy; Ledeganck, Kristien J.; Van Aken, Sara; Vanbesien, Jesse; Gies, Inge; Casteels, Kristina; Massa, Guy; Lysy, Philippe A.; Logghe, Karl; et al. (Frontiers in Pediatrics, 2022)
Objective Real-time continuous glucose monitoring (RT-CGM) can improve metabolic control and quality of life (QoL), but long-term real-world data in children with type 1 diabetes (T1D) are scarce. Over a period of 24 months, we assessed the impact of RT-CGM reimbursement on glycemic control and QoL in children/adolescents with T1D treated with insulin pumps. Research design and methods We conducted a multicenter prospective observational study. Primary endpoint was the change in HbA1c. Secondary endpoints included change in time in hypoglycemia, QoL, hospitalizations for hypoglycemia and/or ketoacidosis and absenteeism (school for children, work for parents). Results Between December 2014 and February 2019, 75 children/adolescents were followed for 12 (n = 62) and 24 months (n = 50). Baseline HbA1c was 7.2 ± 0.7% (55 ± 8mmol/mol) compared to 7.1 ± 0.8% (54 ± 9mmol/mol) at 24 months (p = 1.0). Participants with a baseline HbA1c ≥ 7.5% (n = 27, mean 8.0 ± 0.3%; 64 ± 3mmol/mol) showed an improvement at 4 months (7.6 ± 0.7%; 60 ± 8mmol/mol; p = 0.009) and at 8 months (7.5 ± 0.6%; 58 ± 7mmol/mol; p = 0.006), but not anymore thereafter (endpoint 24 months: 7.7 ± 0.9%; 61 ± 10mmol/mol; p = 0.2). Time in hypoglycemia did not change over time. QoL for parents and children remained stable. Need for assistance by ambulance due to hypoglycemia reduced from 8 to zero times per 100 patient-years (p = 0.02) and work absenteeism for parents decreased from 411 to 214 days per 100 patient-years (p = 0.03), after 24 months. Conclusion RT-CGM in pump-treated children/adolescents with T1D showed a temporary improvement in HbA1c in participants with a baseline HbA1c ≥ 7.5%, without increasing time in hypoglycemia. QoL was not affected. Importantly, RT-CGM reduced the need for assistance by ambulance due to hypoglycemia and reduced work absenteeism for parents after 24 months. Clinical trial registration [ClinicalTrials.gov], identifier [NCT02601729].